Training and development methods and organizational performance: A case of the local government organization in Central Region, Ghana - Godson Kwame Amegayibor (Journal of Social, Humanity, and Education, 2021)
Purpose: Is to investigate the relationship between training and development (T&D) methods and organizational performance in the local government sector, as well as contribute to knowledge. Research Methodology: The study employed a quantitative approach and correlation design, a census sampling method to sample 215 employees, a structured questionnaire to collect data, multiple linear regression to test hypotheses, and the Statistical Package for Social Science (SPSS) version 20 to input, transform and analyze the data. Result: The result shows that training and development (T & D) methods (job orientation, job rotation, workshop & conference, and classroom lectures) had a significant relationship with organizational performance. The findings also revealed that training and development (T & D) methods (job orientation, workshop & conference, and classroom lectures) have a significant relationship with the quality of service delivery. However, job rotation has no relationship with quality service delivery. Limitation: The study's main weakness is that it only looked at four different training and development methods and their impact on organizational performance and service quality. Another flaw in the study is that it only looked at one metropolitan assembly. Contribution: In this regard, metropolitan and municipal assembly executives and managers should consider employing training and development methods that provide stronger predictions to boost the organization’s performance and delivery of quality services to communities. They should train and develop employees within the organization as soon as political power changes hands to enhance organization performance because policy adherence is critical to the organization's performance.